Three-Dimensional Dirac Semimetal/Organic Thin Film Heterojunction Photodetector With Fast Response and High Detectivity - Liu, Qi; Yang, Ming; Zhang, Jiangwei; Yang, Mingliang; Wang, Jun; Zheng, Huajing; Gou, Jun (Frontiers in Physics, 2021)
As a typical three-dimensional Dirac semimetal (3D DSM), Cd3As2 possess ultrahigh carrier mobility, high level of full spectral absorption, fast electron transmission speed, and high photocurrent response, which enable wide applications in infrared photodetector. However, the resistance of pristine Cd3As2 thin film is very small, leading to large dark current of its based detector and limiting the application of the small current response. Hence, we demonstrated heterojunction photodetectors based on n-type 3D DSM Cd3As2 (pristine and Zn doped) and p-type organic (PbPc) by depositing PbPc thin film on Cd3As2 (pristine and Zn doped) thin film using thermal deposition method. These photodetectors can detect the radiation wavelength from 405 nm to 1550 nm at room temperature. It is remarkable that this thin film heterojunction photodetector exhibits high detectivity (1.26×1012 Jones) and fast response time (160 μs) under bias voltage, which is significantly improved versus that of Cd3As2-based devices. The excellent performances are attributed to the strong built-in electric field at the interface of p-n junction, which is beneficial for efficient photocarriers collection and transportation. These results show that DSM/organic thin film heterojunction has excellent performance in the application of photodetectors. By combining 3D DSM with organic to form heterojunction, it provides a feasible solution for high-performance photodetectors.